Electrical Stabilization of a Carbon Nanomaterial in an Aqueous Suspension - Zhdanok, S. A.; Krauklis, A. V.; Kazei, E. A.; Pavlov, A. V.; Shushkov, S. V. (Journal of engineering physics and thermophysics, 2025)
Consideration has been given to the technique of improving the settling (sedimentation) resistance of an aqueous suspension of a carbon nanomaterial due to electrical stabilization through the impact of a gas electric discharge. It has been shown that the solid-phase charging (and discharging) used enables us to promptly change the state of the suspension and to reduce the treatment time without surfactants. A comparison has been made with the functionalization of the carbon nanomaterial by ozonization by the criterion of energy cost reduction.